Aravind Eye Hospital in Chennai : delivering compassionate care in pandemic times - Mukherjee, Saral, (SAGE Business cases., 2024)
Aravind Eye Care System (AECS), a successful eye care system in South India, employed a unique cross-subsidization business model to provide affordable eye care to the disadvantaged and eliminate needless blindness. In 2017, AECS expanded to Chennai, aiming to replicate its success. However, the COVID-19 pandemic in March 2020 led to a drastic drop in patient volume, challenging the model‘s sustainability and the organization‘s mission. The case explores the challenges faced by AECS during March–July 2020, including the risk of blindness for vulnerable patients, employee morale, and operational disruptions. Dr. S. Aravind, Chief Medical Officer of AEH Chennai, had to reinforce the organization‘s culture and adapt the efficiency-oriented model to build resilience. The pandemic revealed societal fault lines and the need for organizational changes.